POLA MUSIMAN KUNJUNGAN WISATAWAN MANCANEGARA AUSTRALIA KE NEGARA INDONESIA, THAILAND, DAN SINGAPURA - Addin Maulana; Chamma Fitri Putri Pradjwalita Koesfardani; Norman Sasono (Jurnal Pariwisata Pesona, 2020)
The number of tourist arrivals is one of the main points in assessing the success of the tourism sector. Because of that, the seasonal pattern of tourist arrivals is an important thing that must be observed in making policies in the field of tourism marketing. Therefore, identifying seasonal patterns will influence the strategy of allocating available resources, especially in markets that have great potential in producing quality tourists like Australia. By using the calculation of Seasonality Ratio, Seasonality Indicator, Gini Coefficients, and Seasonality Index, this study compares the seasonal patterns of Australian tourists arriving in Indonesia with other competing countries, namely Singapore and Thailand. This research has succeeded in identifying that the Seasonality Ratio and Seasonality Indicator values show the pattern of Australian tourists arrives in Indonesia has more fluctuations every month. Despite this, the seasonal level of Australian tourists to Indonesia is low the same as the two other countries. This is seen from the results of the Gini Coefficient calculation in the three countries are below 0.5, or the difference in tourist arrivals per month is not significant. The Seasonality Index indicator shows that January, April, and December are the peak season periods for Australian tourists arriving Singapore and Thailand. However, this is different in Indonesia which is in the off-season phase. Thus, Indonesia has opportunities to optimize Australian tourist arrives in the off-season with the right marketing policies.